Analysis of the Influence of Population Growth, Education, and Health on Poverty in Indonesia from 2018 to 2022 - Septadarman, Adly Caesar; Rambe, Roosemarina Anggraini (East Asian Journal of Multidisciplinary Research, 2024)
The aim of this study is to analyze the influence of population growth, education, and health on poverty in Indonesia. The data used in this research are panel data from 34 provinces in Indonesia spanning the years 2018 to 2022. Poverty is utilized as the dependent variable, while population growth, education, and health serve as independent variables. The analytical method employed is panel data regression. The findings indicate that population growth does not significantly affect poverty in Indonesia, whereas education and health significantly influence poverty in Indonesia from 2018 to 2022.